Caribbean pleasure industry : tourism, sexuality, and AIDS in the Dominican Republic - Padilla, Mark, 1969- (Worlds of desire., 2007)
In recent years, the economy of the Caribbean has become almost completely dependent on international tourism. And today one of the chief ways that foreign visitors there seek pleasure is through prostitution. While much has been written on the female sex workers who service these tourists, Caribbean Pleasure Industry shifts the focus onto the men. Drawing on his groundbreaking ethnographic research in the Dominican Republic, Mark Padilla discovers a complex world where the global political and economic impact of tourism has led to shifting sexual identities andgrowing economic pressures.